The Effect of Administering Herbal Jamu on Egg Quality in PT Sanjaya Satwa Utama Layer Phase Laying Chickens As An Animal Food Security - Anwar, Rohmatul (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2024)
This research aims to determine how much influence herbal ingredients added to drinking water have on the level of internal and external quality of eggs in laying hens. The material used was 700 laying hens aged 51 weeks. The method used was a completely randomized design consisting of two treatments and three replications, the treatment was given in drinking water with each treatment being P0 = without herbs and P1 = drinking water with the addition of herbal ingredients = 1800 liters of drinking water + 600ml of herbal ingredients. The variables observed were internal quality which included the egg white index, egg yolk index and egg Haugh unit. External Quality, namely Shell Thickness and Egg Weight. Based on the research results, the average Internal Quality values ​​for eggs were obtained, namely Egg White Index P0 (0.120) and P1 (0.125). Egg Yolk Index P0 (0.364) and P1 (0.428) and Egg Unit Haugh value P0 (90) and P1 (96). Eternal Quality which includes egg weights P0 (61 grams) and P1 (64 grams), as well as shell thickness values ​​P0 (0.33) P1 (0.34). The conclusion from this research is that giving P0 and P1 does not have a significant effect (P>0.05) on the internal and external quality of eggs, but at each sampling the P1 value is higher than the P0 value on egg quality.